![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
(a2-b2)(a2+ab+b2)(a2-ab+b2)=
3个回答
展开全部
(a2-b2)(a2+ab+b2)(a2-ab+b2)
解,得:
==(a2-b2)[(a2+b2)+ab]*[(a2+b2)-ab]
==(a2-b2)[(a2+b2)^2-a^2b^2]
==(a2-b2)(a^4+2a^2b^2+b^4-a^2b^2)
==(a2-b2)(a^4+a^2b^2+b^4)
==a^6-b^6
解,得:
==(a2-b2)[(a2+b2)+ab]*[(a2+b2)-ab]
==(a2-b2)[(a2+b2)^2-a^2b^2]
==(a2-b2)(a^4+2a^2b^2+b^4-a^2b^2)
==(a2-b2)(a^4+a^2b^2+b^4)
==a^6-b^6
展开全部
(a2-b2)(a2+ab+b2)(a2-ab+b2)
=(a-b)(a2+ab+b2)(a+b)(a2-ab+b2)
=(a³-b³)(a³+b³)
=a^6-b^6
=(a-b)(a2+ab+b2)(a+b)(a2-ab+b2)
=(a³-b³)(a³+b³)
=a^6-b^6
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询